What does good look like? Officers’ perception of the ideal law enforcer - Bell, Stephen W.; Cliff, Jennifer L. (Frontiers in Sociology, 2025)
The purpose of this basic qualitative study was to explore how law enforcement officers describe the attributes, characteristics, and qualities that combine to form the archetype of the ideal law enforcer. Convenience sampling was used to recruit 22 law enforcement officers. Data were collected through semi-structured interviews and thematically analyzed. While the participating officers were candid about the traits they perceived to be ideal among law enforcers, interestingly, these officers tended to avoid topics of physicality. The bulk of the coded data revealed themes that related to personality characteristics. Findings revealed that law enforcement officers categorized their self-described ideal traits of other officers into three primary themes: (1) Humanity and Emotional Intelligence, (2) Moral Courage, and (3) Resilience and Occupational Effectiveness.